How do mid-senior multinational officers perceive shared leadership for military teams? A qualitative study - Cakiroglu, Serkan (2020)
Purpose – The purpose of this study is to explore the military team members’ (mid-senior multinational officers’) perceptions of shared leadership and analyze the facilitation of shared leadership in military teams. Design/methodology/approach – The sample size was 20 interviewees that participants must hold leadership positions at the mid-senior management level and from NATO member countries. To analyze the data, the authors used Gioia’s thematic analysis methodology (Gioia et al., 2013) and manual coding rather than computer usage for the analysis, due to the small data pool and their proficiency in literature. Findings – Complexity and the new information era force military organizations toward the change and that with shared leadership they can even change the organization’s culture. The final framework highlights five main dimensions that emerged from mid-multinational military officers’ experience: driving forces of change, triggers to shared leadership, specific cases shared leadership, operational team environment and operational team characteristics. Results of the study supported that driving forces of change comprised the primary factor affecting shared leadership in military project teams. Practical implications – The Headquarter environment (strategic and operational planning) and planning were critical factors for the successful implementation and development of shared leadership in military project teams. Thus, military organizations could easily implement the shared leadership approach in the military research teams and planning teams. Originality/value – The authors present a framework of leadership change context for military teams, which depicts how shared leadership could be implemented differently in military teams.